EFFECTIVE TEACHING AND LANGUAGE LEARNING MOTIVATION: A STUDY ON THE INTERCONNECTION - Kafi, Zeinab; Motallebzadeh, Khalil (University of Kuningan, 2015)
The present study aimed at examining the relationship between EFL teachers’ effective teaching and the language learning motivation of Iranian EFL learners whose English proficiency was upper-intermediate and above. To this end, 150 upper-intermediate and advance EFL students, from some language schools in Mashhad, Iran participated in the study. The participants were firstly asked to fill out a researcher made questionnaire which aimed at checking their opinions on how effective they considered their teachers in teaching (Effective Teaching Questionnaire). Afterwards, the same students were asked to fill out a questionnaire that investigated how much motivated they were for learning English (Language Learning Motivation Questionnaire). These questionnaires were validated by two experts in the field, also their reliability, using Cronbach's Alpha, was estimated to be .87 and .80 respectively. Afterwards the relation between teachers’ effectiveness in teaching and the extent to which students were motivated as a result was investigated. For measuring the probable relation, correlation as well as multiple regressions was run for analysis of the obtained data. The results exhibited the existence of a positive relation between the two.Keywords: Effective teaching, motivation, EFL learners, EFL teachers